Sex Hormones and Gender Role Relate to Gray Matter Volumes in Sexually Dimorphic Brain Areas - Pletzer, Belinda (Frontiers in Neuroscience, 2019)
The present study investigates the relationship of circulating sex hormone levels and gender role to grey matter volumes in sexually dimorphic brain areas and explores, whether these relationships are modulated by biological sex (as assigned at birth based on sexual anatomy) or oral contraceptive (OC) use. It was hypothesized that testosterone and masculinity relate positively to grey matter volumes in areas that are typically larger in men, like the hippocampus or cerebellum, while estradiol/progesterone and femininity relate positively to grey matter volumes in the frontal cortex. To that end, high resolution structural MRI scans, sex hormone levels and gender role self-assessments were obtained in a large sample 89 men, 89 naturally cycling (NC) women and 60 OC users. Men showed larger regional grey matter volumes than women in the cerebellum and bilateral clusters spanning the putamen and parts of the hippocampi/parahippocampi and fusiform gyri. In accordance with our hypotheses, a significant positive association of testosterone to hippocampal volumes was observed in women irrespective of OC use. Participant’s self-reported femininity was significantly positively associated with grey matter volumes in the left middle frontal gyrus in men. In addition several differences between OC-users and NC women were identified.